Prevalence of Metabolic Syndrome based on Six Definitions in SouthwesternIran: A Cross- Sectional Study from the Hoveyzeh Cohort Study - Seyed Mohammad Bahrainian; Leila Moadi; Meysam Alipour; Amaghan Moavej Aleali; Hajieh Shahbazian (Shiraz University of Medical Sciences, 2024)
Background: Metabolic syndrome (MetS) is identified by an accumulation of signs of a metabolic disorder and has become a growing problem in recent years due to its major public health risks. Therefore, this study aimed to assess the prevalence of MetS and its components based on six definitions.Methods: In this cross-sectional study, 8596 individuals (2966 males and 5630 females) aged 35-70 years were recruited from the Hoveyzeh Cohort Center from May 2016 to August 2018. The diagnostic criteria proposed by the Joint Interim Statement (JIS), the Regional JIS (RJIS), the American Heart Association/ National Heart, Lung, and Blood Institute (AHA/NHLBI), the International Diabetes Federation (IDF), the Regional IDF (RIDF), and Adult Treatment Panel III (ATP III) were used.Results: The prevalence of MetS was 40.7% (ATP III), 47.3% (IDF), 40.8% (RIDF), 44.2% (AHA/NHLBI), 48.9% (JIS), and 44.7% (RJIS). Overall, males and females showed a higher prevalence of MetS based on the JIS criteria. Based on gender, the prevalence of MetS was higher in women than in men according to all six definitions. The most common component for all deinitions was TGs domain. Also, all four MetS components were higher in people living in urban areas than in those living in rural areas.Conclusion: The results of this study suggest that a higher prevalence of MetS is related to the JIS definition; this may also indicate the importance of assessing MetS based on this definition in clinical practice in the southern Iranian population.